Trade Liberalization and Pollution: Evidence from the Philippines - Caesar B. Cororaton; Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2001)
The paper assesses the impact of trade reforms in the Philippines on pollution using CGE model simulations and two industry case studies on sugar milling and refining and cement manufacturing. Generally, trade reform is output augmenting and welfare improving. The overall impact on pollution is very small. Output taxes to reduce pollution are ineffective. They wipe out the potential gain from trade reforms. The case studies support the simulation results. Trade liberalization leads to more competition, improvements in efficiency, and increased foreign investment. All this increased environmental awareness. It accelerated the promotion and production of good environmental systems and adoption of ISO standards.
Keywords: 330; trade and pollution; Handelsliberalisierung; Umweltbelastung; Philippinen